Vermicomposted corn waste in the organic cultivation of cherry tomato seedlings and its effects on the soil-plant system - Jos ́e Matheus de Oliveira; Jefferson Campos Silva; Andreza Jayane Nunes de Siqueira; Ramom Rachide Nunes (International Journal of Recycling of Organic Waste in Agriculture)
Propose: In this study, vermicomposted corn waste was applied to the organic cultivation of cherry tomato seedlings under the edaphoclimatic conditions of the Brazilian semiarid region, and the effects were evaluated in the soilâplant system.